2015
DOI: 10.1007/s11630-015-0790-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-axisymmetric flow characteristics in centrifugal compressor

Abstract: The flow field distribution in centrifugal compressor is significantly affected by the non-axisymmetric geometry structure of the volute. The experimental and numerical simulation methods were adopted in this work to study the compressor flow field distribution with different flow conditions. The results show that the pressure distribution in volute is characterized by the circumferential non-uniform phenomenon and the pressure fluctuation on the high static pressure zone propagates reversely to upstream, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The experiments were conducted at the Beijing Institute of Technology. More detailed information about the test setup can be found in Yang et al 20 and Wang et al 21…”
Section: Validation Of Similarity Schemementioning
confidence: 99%
See 3 more Smart Citations
“…The experiments were conducted at the Beijing Institute of Technology. More detailed information about the test setup can be found in Yang et al 20 and Wang et al 21…”
Section: Validation Of Similarity Schemementioning
confidence: 99%
“…The experiments were conducted at the Beijing Institute of Technology. More detailed information about the test setup can be found in Yang et al 20 and Wang et al 21 As shown in Figure 8, the compressor tested has the same working fluid and boundary conditions. In addition, the rotational speed range and pressure ratio are similar.…”
Section: Numerical Schemementioning
confidence: 99%
See 2 more Smart Citations
“…Under the action of the volute, the circumferential flow nonuniformities in a centrifugal compressor existed in the entire flow range [28][29][30] and more near the choke. As the compressor was throttled from the near choke to design condition, the nonuniformity in the circumferential distribution of static pressure decreased gradually.…”
Section: Introductionmentioning
confidence: 99%